Censored : a literary history of subversion and control - Fellion, Matthew; Inglis, Katherine (McGill-Queen's University Press, 2017)
"When Henry Vizetelly was imprisoned in 1889 for publishing the novels of Émile Zola in English, the problem was not just Zola's French candour about sex--it was that Vizetelly's books were cheap, and ordinary people could read them. Censored exposes the role that power plays in censorship. In twenty-five chapters focusing on a wide range of texts, including the Bible, slave narratives, modernist classics, comic books, and Chicana/o literature, Matthew Fellion and Katherine Inglis chart the forces that have driven censorship in the United Kingdom and the United States for over six hundred years, from fears of civil unrest and corruptible youth to the oppression of various groups--religious and political dissidents, same-sex lovers, the working class, immigrants, women, racialized people, and those who have been incarcerated or enslaved. The authors also consider the weight of speech, and when restraints might be justified. Rich with illustrations that bring to life the personalities and the books that feature in its stories, Censored takes readers behind the scenes into the courtroom battles, legislative debates, public campaigns, and private exchanges that have shaped the course of literature. A vital reminder that the freedom of speech has always been fragile and never enjoyed equally by all, Censored offers lessons from the past to guard against threats to literature in a new political era."--